Pengaruh Citra Merek dan Kualitas Produk Terhadap Keputusan Pembelian Point Coffee di Indomaret Diponegoro Kota Surabaya - Nidya Putri Octavia (Tamilis Synex: Multidimensional Collaboration, 2023)
This study aims to find out more about the "Influence of Brand Image and Product Quality on Purchasing Decisions of Pointcoffee at Indomaret Diponegoro, Surabaya City" in accordance with the main problem raised, namely the relationship between Brand Image and Product Quality in Purchasing Decisions of a Coffee branded Pointcoffee. This research method is a quantitative method using a questionnaire. The object of this study is Point Coffee consumers at Indomaret Diponegoro, Surabaya City and a sample of 100 respondents was obtained. Hypothesis testing in this study uses the Variable and Reliable Test, Classical Assumption Test, Multiple Linear Test, T Test, F Test and Determinant Coefficient Test using IBM SPSS. And the results of this study indicate that the variables of Brand Image and Product Quality have a positive and significant effect on Purchasing Decisions.